Misdiagnosis of Myocardial Infarction Related to Limitations of the Current Regulatory Approach to Define Clinical Decision Values for Cardiac Troponin. Issue 23 (9th June 2015) - Wildi, Karin; Gimenez, Maria Rubini; Twerenbold, Raphael; Reichlin, Tobias; Jaeger, Cedric; Heinzelmann, Amely; Arnold, Christiane; Nelles, Berit; Druey, Sophie; Haaf, Philip; Hillinger, Petra; Schaerli, Nicolas; et al.
Abstract : Background—: Misdiagnosis of acute myocardial infarction (AMI) may significantly harm patients and may result from inappropriate clinical decision values (CDVs) for cardiac troponin (cTn) owing to limitations in the current regulatory process. Methods and Results—: In an international, prospective, multicenter study, we quantified the incidence of inconsistencies in the diagnosis of AMI using fully characterized and clinically available high-sensitivity (hs) cTn assays (hs-cTnI, Abbott; hs-cTnT, Roche) among 2300 consecutive patients with suspected AMI. We hypothesized that the approved CDVs for the 2 assays are not biologically equivalent and might therefore contribute to inconsistencies in the diagnosis of AMI. Findings were validated by use of sex-specific CDVs and parallel measurements of other hs-cTnI assays. AMI was the adjudicated diagnosis in 473 patients (21%). Among these, 86 patients (18.2%) had inconsistent diagnoses when the approved uniform CDV was used. When sex-specific CDVs were used, 14.1% of female and 22.7% of male AMI patients had inconsistent diagnoses. Using biologically equivalent CDV reduced inconsistencies to 10% ( P <0.001). These findings were confirmed with parallel measurements of other hs-cTn assays. The incidence of inconsistencies was only 7.0% for assays with CDVs that were nearly biologically equivalent. Patients with inconsistent AMI had long-term mortality comparable to that of patients with consistent diagnoses ( P =NS) and a trend toward higher long-term mortality than patients diagnosed with unstable angina ( P =0.05). Conclusions—: Currently approved CDVs are not biologically equivalent and contribute to major inconsistencies in the diagnosis of AMI. One of 5 AMI patients will receive a diagnosis other than AMI if managed with the alternative hs-cTn assay. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00470587. Abstract : Supplemental Digital Content is available in the text.